MASYĀKILU TA’LĪMI ‘ILMI AL-ṢORFI BI MADRASAH AL-IRSYĀD AL-MUTAWASSIṬAH AL-ISLĀMIYYAH - Maulana, Muhammad Rifqi; Ilhami, Hamidi; Shodiqin, Rahmat (STIQ Amuntai, 2023)
Knowledge Sharf is widely taught in schools and Islamic boarding schools in Indonesia, one of the many learning sciences Sharf located in the city of Martapura in Ma'had Bakkah Martapura, South Kalimantan. Ma'had Bakkah focuses on the Tahfizul Qur'an, in which students must memorize the Quran and there is MTs Al-Irsyad Tengaran 8. Researchers have conducted interviews with Faisal Abdurrahim, Principal of MTs Al-Irsyad Tengaran 8 and Muhammad Hafidz Anshari, teacher Sharf grade 9 found learning problems Sharf to the students. This field research applies qualitative research with the case study method, the source of data collected through 3 ways: observation, interviews, and documentation. The subjects of this study were students from public elementary school graduates who had memorized 3 chapters of the Quran and Sharf teachers who had taught for 5 years at MTs Al-Irsyad Tengaran 8 Ma'had Bakkah and the object of this research was learning problems Sharf is tashrif al-af’al on book kitab al-tashrif from volume 1, 2, 3. The results of this study are: 1) Learning Sharf and its components. The goal is that students can change words with tashrif. The material focuses on the Book of Al-Tashrif. The media used are books, blackboards, and markers. The method used MethodAl-Sam’iyyah Al-Syafahiyyah. Evaluation includes evaluation of learning outcomes and evaluation of the learning process. 2) There are 23 learning problems for students at this Islamic junior high school.